2023
DOI: 10.1021/acssuschemeng.3c03796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mechanical Refining Conditions on the Energy Consumption, Enzymatic Digestibility, and Economics of Sugar Production from Corn Stover

Yudong Li,
Ryan Davis,
Eric C. D. Tan
et al.

Abstract: Reducing the energy intensity of the mechanical refining-based pretreatment process for producing lignocellulosicderived sugars without significantly affecting enzymatic hydrolysis sugar yields is challenging. This work investigated the impact of different refining conditions on energy consumption, enzymatic sugar yields, minimum sugar selling price, and environmental impacts for the conversion of corn stover to sugars. A positive proportionate correlation between specific energy consumption and enzymatic suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Various types of pretreatment techniques have been studied with the goal of improving the digestibility of these polymers to make the cellulose more accessible in LBs for more efficient conversion into soluble sugars. The implementation of mechanical pretreatment techniques has gained popularity in recent years [8][9][10][11] due to the reductions in energy consumption and the increased benefits that these techniques provide in breaking up the structural components of LBs. The main advantages that mechanical pretreatment techniques provide are the ability to alter the properties of the lignocellulose through cutting, shearing, and compression, which make enzymes more accessible for hydrolysis conversion [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of pretreatment techniques have been studied with the goal of improving the digestibility of these polymers to make the cellulose more accessible in LBs for more efficient conversion into soluble sugars. The implementation of mechanical pretreatment techniques has gained popularity in recent years [8][9][10][11] due to the reductions in energy consumption and the increased benefits that these techniques provide in breaking up the structural components of LBs. The main advantages that mechanical pretreatment techniques provide are the ability to alter the properties of the lignocellulose through cutting, shearing, and compression, which make enzymes more accessible for hydrolysis conversion [12].…”
Section: Introductionmentioning
confidence: 99%
“…Deacetylation and mechanical refining pretreatment (DMR) is one of the treatment processes which incorporates two mechanical refinement steps, including disk refining and Szego milling [10,11,13,14]. Researchers at the National Renewable Energy Laboratory (NREL, Golden, CO, USA) have shown that the inclusion of this technique within the pretreatment cycle has improved sugar yields and concentrations from LBs including corn stover, switchgrass, sorghum, and blends of these LBs [9,10,15].…”
Section: Introductionmentioning
confidence: 99%